Enhancing Self-Awareness to Prevent Gender-Based and Sexual Violence on Campus through Interprofessional Education Intervention: Self-Awareness to Prevent Gender-Based and Sexual Violence on Campus - Saudah, Noer; Abidin, Chasiru Zainal; Lestari, Indah; Andarini, Esti; Nadhiroh, A'im Matun; Frilasari, Heni; Lutfi Sandi, Yudisa Diaz (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2025)
Gender-based sexual violence on campus is a serious issue and is a less serious concern. Students tend to lack an understanding of sexual issues caused by the culture on campus that disfavors the victim by the theory of power relations and a feminist perspective. Students’ knowledge and awareness of gender-based sexual violence on campuses need to be improved. This study assesses students’ self-awareness due to health promotion provided through the Interprofessional Education (IPE) approach. A quasi-experiment with a pre-post-test design was conducted to evaluate 144 students through purposive sampling. The questionnaire adapted from the Situational Self-Awareness Scale (SSAS) was utilized to collect the data. There was a significant improvement in self-awareness (p < 0.001 and t-value= 25.68) after receiving IPE among students. Providing health education with an IPE approach is an effective strategy for raising undergraduate students' awareness of gender-based sexual violence on campus. This intervention may help develop the concept of cooperation and collaboration between health professionals to prepare and create standard measures for preventing and addressing cases of gender-based sexual violence on campus.